FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN GANGGUAN PENDENGARAN PADA TENAGA KERJA PT BNT BENGKULU TENGAH - Mulyati, Sri (JURNAL MEDIA KESEHATAN, 2015)
Continuous and uncertainty noise exposure have possibility in disruption of hearing.These disorders can be both temporary and permanent, besides the noise also can lead to a senseof uncomfortable, anxiety, stress, the increased of heart rate, as well as other disorders of OccupationalAccidents (KAK), Occupational Diseases and Diseases of Employment increased in thelast three years since the year 2012 until 2014 amounted to 5%, 7% and 10%. This study aimedto know the factors associated with hearing loss in labor of PT BNT. This research used observationalwith cross sectional approach. The sample in this research amounted to 56 peoplewith purposive sampling technique. Data were analised using univariat, bivariat Chi Squareand simple multivariate regress logistic regression. There was a significant relationship amongthe use of PPE of employment, labor knowledge of employment, age of employment, the periodof employment, the level of noise with hearing loss of labor of PT BNT. The most dominant factoraffecting hearing loss occurs was work period with Exp (B) 23.889. The use of Personal ProtectionTool for workers, especially Ears Protection in every working chance in the process ofcontinuous employment, increase the habit of using whether with or without supervision, maintainPersonal Protection Tool individually and continuously and for PT BNT In the process ofpersonal protective equipment should be fully prepared, especially Ear Protection Tool Equipment,check the health workforce in the process periodically and regularly, especially the auditorysystem, Enforce reward for workers who use Personal Protection Tool continuously and punishmentfor workers who often do not use Personal Protection Tool.